PENGARUH STRES KERJA, LINGKUNGAN KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA GURU PADA SMK NEGERI 1 PONOROGO - Siti Munawaroh; Umi Farida; Sri Hartono (STIE Trisna Negara OKU Timur, 2023)
This study aims to determine the effect of work stress, work environment, and leadership style on teacher job satisfaction at SMK Negeri 1 Ponorogo. The population in this study were all teachers at SMK Negeri 1 Ponorogo, totaling 77 people. and the sample used was 30 respondents. The sampling technique in this study was Nonprobability Sampling using Saturated Sampling. This research uses quantitative research methods. Data collection techniques using observation, interviews/interviews, and questionnaires. To test the instrument using the validity test and reliability test. The data analysis technique uses multiple linear regression analysis and analysis of the coefficient of determination (R2). The results showed that 1) Job Stress has a negative effect on Job Satisfaction with a significance of 0.046. 2) Work environment has a positive effect on job satisfaction with a significance of 0.014. 3) Leadership style has a positive effect on job satisfaction with a significant value of 0.000. 4) Job Stress, Work Environment, and Leadership Style simultaneously influence Job Satisfaction by 49.3% and the remaining 50.7% are influenced by other variables outside the variables in this study.